2020
DOI: 10.1097/brs.0000000000003603
|View full text |Cite
|
Sign up to set email alerts
|

2021 Young Investigator Award Winner: Anatomic Gradients in the Microbiology of Spinal Fusion Surgical Site Infection and Resistance to Surgical Antimicrobial Prophylaxis

Abstract: Study Design. Retrospective hospital-registry study. Objective. To characterize the microbial epidemiology of surgical site infection (SSI) in spinal fusion surgery and the burden of resistance to standard surgical antibiotic prophylaxis. Summary of Background Data. SSI persists as a leading complication of spinal fusion surgery despite the growth of enhanced recovery programs and improvements in other measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 23 publications
2
47
0
Order By: Relevance
“…When examining the relationship between anatomic region and the microbiology of SSI following spinal fusions, patients who were found to have mixed infections were more likely to have undergone thoracic fusion, while patients who had gram-positive and gram-negative infections were more likely to have undergone cervical and lumbar fusion, respectively. This finding is consistent with previous studies, with 2 retrospective studies reporting greater proportions of gram-positive infections occurring after cervical fusions, while gram-negative infections followed lumbar/lumbosacral fusion 10,11. A likely explanation for this finding is due to the natural microbiome of the skin and intestinal tract; gram-positive species are among the most common skin flora, while gram-negative species are among the most common intestinal flora, frequently identified near the lumbosacral region 18,19.…”
Section: Discussionsupporting
confidence: 91%
“…When examining the relationship between anatomic region and the microbiology of SSI following spinal fusions, patients who were found to have mixed infections were more likely to have undergone thoracic fusion, while patients who had gram-positive and gram-negative infections were more likely to have undergone cervical and lumbar fusion, respectively. This finding is consistent with previous studies, with 2 retrospective studies reporting greater proportions of gram-positive infections occurring after cervical fusions, while gram-negative infections followed lumbar/lumbosacral fusion 10,11. A likely explanation for this finding is due to the natural microbiome of the skin and intestinal tract; gram-positive species are among the most common skin flora, while gram-negative species are among the most common intestinal flora, frequently identified near the lumbosacral region 18,19.…”
Section: Discussionsupporting
confidence: 91%
“…In a similar study by Long, et al, the authors performed a retrospective review on 6727 patients. 11 The authors noted that Cephalosporin-resistant gram-negative infection was common at lumbosacral levels. And the authors suggested "novel approaches to prophylaxis and prevention should be prioritized in this population".…”
Section: Discussionmentioning
confidence: 99%
“…These authors noted “ gram-negative organisms accounted for a sizeable portion of SSI, particularly among lower lumbar and sacral spine surgical procedures”. In a similar study by Long, et al, the authors performed a retrospective review on 6727 patients [11] . The authors noted that Cephalosporin-resistant gram-negative infection was common at lumbosacral levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations